2004
DOI: 10.1086/424956
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Algorithm–based Exploration of Three Filament Models: A Case for the Magnetic Support of the G11.11−0.12 Infrared‐dark Cloud

Abstract: The G11.11-0.12 infrared-dark cloud has a filamentary appearance, both in extinction against the diffuse infrared emission of the Galactic plane and in emission at 850µm. We use a novel computational technique based on an advanced genetic algorithm to explore thoroughly 3 different models of self-gravitating, pressure truncated filaments and to constrain their parameters. Specifically, the models tested are the non-magnetic Ostriker (1964) model, a generalized version of the magnetic Stodólkiewicz (1963) model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…James Clerk Maxwell Telescope submillimetre studies of Orion B (Mitchell et al 2001) reveal a plethora of filamentary structures and their embedded cores. This pattern is also seen in the observational studies by Fiege et al (2004), wherein a few bright cores are seen to be embedded in a larger, isolated filamentary structure. Similar results are also seen in more embedded regions such as the Lupus 3 cloud, where strong links between filaments and emerging star clusters are observed (Teixeira, Lada & Alves 2005).…”
Section: Introductionsupporting
confidence: 71%
“…James Clerk Maxwell Telescope submillimetre studies of Orion B (Mitchell et al 2001) reveal a plethora of filamentary structures and their embedded cores. This pattern is also seen in the observational studies by Fiege et al (2004), wherein a few bright cores are seen to be embedded in a larger, isolated filamentary structure. Similar results are also seen in more embedded regions such as the Lupus 3 cloud, where strong links between filaments and emerging star clusters are observed (Teixeira, Lada & Alves 2005).…”
Section: Introductionsupporting
confidence: 71%
“…The criteria for a filament are different for those of a uniform medium (Larson 1985). Theoretical models for filaments range from a simple non-magnetic isothermal filament (Ostriker 1964) to magnetised filaments with helical fields which can be toroidal or poloidal or both (Tilley & Pudritz 2003;Fiege & Pudritz 2000;Fiege et al 2004). A key prediction from these models is the ratio of the mass per unit length m to the cylindrical virial mass per unit length m vir , which is given by…”
Section: Filamentsmentioning
confidence: 99%
“…1 and 4). Using a sophisticated computational technique Fiege et al (2004) compared observations to three different models of self-gravitating, pressure-truncated filaments, namely the nonmagnetic Ostriker (1964) model, and two magnetic models from the literature. Analysing the 850µm SCUBA observations of G11.11-0.12, Johnstone et al (2003) concluded that this source has a much steeper r −α , (α > ∼ 3) radial density profile than other (lower moss, lower extinction) filaments, where the density varies approximately as r −2 , This steep density profile is consistent with the Ostriker model.…”
Section: Morphologymentioning
confidence: 99%